Anteseden Halal Purchase Behavior - Sarah Gabriella; Kurniawati Kurniawati (Benefit: Jurnal Manajemen dan Bisnis, 2021)
There are several determining factors to analyze this research. Among others are religious factors, attitudes, purchase intentions, personal norms, and halal purchase behavior. Methodology – Using hypothesis testing carried out using the structural equation model (SEM) method with the help of AMOS software. This study used 237 respondents using the purposive random sampling method. The sample used in this study were customers who had purchased halal cosmetic products in the last 6 (six) months. Results - Variables that influence in this research are Personal Norm variable on Attitude, Personal Norm variable on Purchase Intention, Personal Norm variable on Halal Purchasing Behavior, Attitude variable on Purchase Intention, Purchase Intention variable on Halal Purchasing Behavior and the Influence of Religion on Purchase Intention, there is an influence of Personal Norms on Purchase Intention, when mediated by Attitude, there is an effect of Attitude on Halal Buying Behavior when mediated by Purchase Intention. Implications - Users of halal cosmetic products must pay more attention to how to improve religion, personal norms, attitudes, purchase intentions, and halal purchasing behavior in purchasing halal cosmetic products so that consumers feel satisfied after purchasing halal cosmetic products. For further research, you can also add and analyze additional factors that affect the quality of halal products, experience, and image of products.